Particular qualities of the treatment of persons who have committed sexual offenses - Kozeratska, Олена (Psychosomatic Medicine and General Practice, 2021)
Background. The question of the treatment of persons who accomplished sexual crimes continues to be discussed by researches around the world. Mark certain insufficiency of preparation of specialists in relation to an estimation and treatment of sexual disorders in medical and psychiatric establishments, and even in judicial psychiatric associations, that understanding, that treatment of sexual criminals is accessible and can be successful and effective needs a subsequent ground. Current criteria of the force usage of medical care are developed not enough. Aim. To find out the criteria of application of the forced measures of medical character This research is devoted to solving scientific and practical problems, which is to develop a forensic-psychiatric expert evaluation of persons who have committed sexual criminal offences. Materials and methods. The paper presents the results of a scientific study conducted as part of the dissertation “Forensіc psychіatrіc evaluatіon of persons who have sexual offences”. To achieve the goal of the study, the author analyzed 287 sub-experts who committed sexual offences and were on forensic psychiatric examination (FPE) at the Kyiv City FPE Center from 2000 to 2015 (16 years). In order to determine the relationship between the degree of violation of the ability to understand their actions, manage them and resolve expert issues, all observations were divided into 2 groups of comparison: 1 – 200 observations (sub-experts, considered “sane”); 2 – 14 (sub-experts, recognized as “insane”); 3 – 73 (“limited sanity”), this group was formed artificially from the group of “sane”, based on the concept of “limited sanity”. Research methods used in the work: information-analytical, socio-demographic, clinical-psychopathological, experimental-psychological, expert, situational analysis, statistical. Results. The criterion for the application of coercive measures of a medical nature (CMMN) in the form of a referral to a specialized psychiatric institution is the recognition of a person as “insane”, the provision of compulsory outpatient care. Conclusions. The identification of criteria for choosing the right forced medical health care type, i.e., validity and sufficiency of the recommended forced measure of a medical character, is needed to increase a quality upgrading prophylactic measures in the conditions of the forced treatment.